2001
DOI: 10.1074/jbc.m106211200
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Response Elements Alter Coactivator Recruitment through Allosteric Modulation of Estrogen Receptor β Conformation

Abstract: Estrogen receptor ␤ (ER␤) activates transcription by binding to estrogen response elements (EREs) and coactivator proteins that act as bridging proteins between the receptor and the basal transcription machinery. Although the imperfect vitellogenin B1, pS2, and oxytocin (OT) EREs each differ from the consensus vitellogenin A2 ERE sequence by a single base pair, ER␤ activates transcription of reporter plasmids containing A2, pS2, B1, and OT EREs to different extents. To explain how these differences in transact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 44 publications
4
40
0
Order By: Relevance
“…Evidence for intra-domain communication within the oestrogen receptor (ER) comes initially from the use of domain-specific antibodies (Traish & Pavao 1996), while altered protease sensitivity reveals altered receptor conformation on different oestrogen response elements (ERE) for both ER and ER (Wood et al 1998, Klinge et al 2001, Loven et al 2001a). In the case of ER bound to different EREs distinct patterns of recruitment of members of the p160 coactivator family were observed (Loven et al 2001b). With ER it was clear that coactivator binding stabilised interactions with DNA; however differences in coactivator recruitment were less obvious (Wood et al 2001).…”
Section: Discussionmentioning
confidence: 92%
“…Evidence for intra-domain communication within the oestrogen receptor (ER) comes initially from the use of domain-specific antibodies (Traish & Pavao 1996), while altered protease sensitivity reveals altered receptor conformation on different oestrogen response elements (ERE) for both ER and ER (Wood et al 1998, Klinge et al 2001, Loven et al 2001a). In the case of ER bound to different EREs distinct patterns of recruitment of members of the p160 coactivator family were observed (Loven et al 2001b). With ER it was clear that coactivator binding stabilised interactions with DNA; however differences in coactivator recruitment were less obvious (Wood et al 2001).…”
Section: Discussionmentioning
confidence: 92%
“…Notably, PERC seems to prefer promoters with multiple sites, such as the dimerized EREs, or the C3 promoter that has at least three EREs (40). Different response elements may induce distinct nuclear receptor conformations and thereby influence either the recruitment of the coactivators or the activity of the recruited coactivators (45,46). An additional context that reveals differences in PERC and PGC-1 function is the ability of the two coactivators to promote the agonistic effect of the partial agonist tamoxifen.…”
Section: Perc and Pgc-1 Confer Distinct Functional Properties To Ligamentioning
confidence: 99%
“…These experiments combined with our GST-MPG pull-down studies indicate that ERE-containing DNA increases the interaction of ER␣ with MPG. We have previously demonstrated that DNA acts as an allosteric modulator of ER␣ conformation and thereby influences the interaction of the receptor with coregulatory proteins (5,25,27). Our current studies suggest that the interaction of the receptor with the ERE enhances the recruitment of MPG to estrogen-responsive genes.…”
mentioning
confidence: 57%